The effectiveness of promotional tools in enhancing customer awareness towards Bulatan Mekar Sdn Bhd / Norsyakira Norman - Norman, Norsyakira (2009)
Bulatan Mekar Sdn Bhd is the developer company who focus on developing land and property for Bumiputera Muslim residents. Bulatan Mekar Sdn Bhd has taken the challenge to enter the market directly to serve the housing development even though the industry is really tough and has a strong competition for those rivals to survive. The company was incorporated in Malaysia since 22nd March 2000 under the Companies Act, 1965 as a private limited company. It is formed to fulfill the competences of Bumiputera Muslim involvement in the property development industry. The main purpose of this study is that researcher wants to know the most effective tools that can be used for the company to increase their customer awareness. This is the most important element for the company because customer is the key of the success in the business. So to achieve the goals, company must first know who their target consumer is and how to make them aware about the products before they can persuade customers to make purchase from the company.